Is Your House a Brothel? Prostitution Policy, Provision of Sex Services from Home, and the Maintenance of Respectable Domesticity. Issue 1 (28th August 2014) - Prior, Jason; Crofts, Penny
Abstract : Policy debates on commercial sex services provide increasingly complex insights into work on the street and in large commercial sex premises, yet remain largely silent on the contribution of the domestic realm to commercial sex, despite estimates that it accounts for a significant proportion of all commercial sex transactions. Policies that affect home-based sex work are ambiguous and at times contradictory, veering from the promotion of working from home to anxieties about the assumed offensiveness of sex work. These policies have been often developed without direct consideration of home-based sex work and in the absence of evidence. Remedying this silence, this article analyses policy development for, and the experiences of, home-based sex workers in New South Wales (NSW), Australia. The article concludes that working from home provides sex workers with opportunities for autonomy and wellbeing that are not available in other sex service environments, with minimal amenity impacts to the community.